Efeitos da temperatura de secagem nos teores de compostos cianogênicos totais e fibra alimentar de casca de maracujá - DEUS, Gilciléia Inácio de (2011)
Brazil is one of the world s largest producers of yellow passion fruit (Passiflora edulis), that are mainly consumed fresh or used to produce juice. Studies indicate the use of yellow passion fruit skin in jam, sweets, cereal bars, cereals, and cookies especially due to its soluble and insoluble fiber content. Other studies have shown that yellow passion fruit skin contains cyanogenic compounds that may prooke intoxication when ingested above the threshold dose. The present work aim to assess the effects of different drying temperatures on the physical and chemical properties and total content of cyanogenic compounds in yellow passion fruit skin. The fruits were purchased at Goiania´s market and their characterization included visual evaluation of the color, average weight and proportion skin:pulp. The skin was sanitized, triturated, dried at 30°C or 45°C or 60°C to produce flour, in three repetitions for each temperature. The flour obtained at each drying temperature, and a commercial brand of yellow passion fruit flour were analyzed as to moisture, water activity, pH, titratable acidity, and total content of cyanogenic compounds. Yellow skins presenting small green spots characterize ripening stage 6 and were observed in 35.00% of the fruits. Average fruit weight was 142.06±31.95 g, 56.51±11.92% corresponded to the skin and 42.88±11.86% to the pulp with seeds. The increase in temperature caused significant decrease in moisture, equilibrium moisture, and water activity. Titratable acidity and pH results did not show any trends in relation to temperature variation. Taking into consideration the results of the dry products, drying treatments at 30°C, 45°C, and 60°C reduced total content of cyanogenic compounds by 84.98%, 85.75%, and 95.41%, respectively. Yellow passion fruit flour dried at 60°C presented 51.39% less cyanogenic compounds than the commercial brand. All drying temperatures caused alterations in the physical and chemical properties of the final product, but the treatment at 60ºC provoked the highest reduction in total content of cyanogenic compounds.